Antitumor activity of a sp. isolated from polluted soil - Xin-Guo Zhang; Zi-Yu Liu; Jin-Wen Liu; Yan-Long Zeng; Guang-Jun Guo; Qiao-Yun Sun (Tumor Biology, 2017)
The actinomycetes strain, lut0910 , was isolated from polluted soil and identified as the Rhodococcus species with 99% similarity based on the sequence analysis of 16S recombinant DNA. The extract of this strain demonstrated in vivo and in vitro antitumor activity. The treatment of two human cancer cell lines, hepatocellular carcinoma HepG2 and cervical carcinoma Hela cells, with the lut0910 extract caused the delay in cell propagation in a dose-dependent manner with an IC 50 of 73.39 and 33.09 µg/mL, respectively. Also, the oral administration of lut0910 extract to the mice with a solid tumor resulted in the inhibition of tumor growth in comparison with a placebo group. The thymus and spleen indexes were significantly increased in mice groups treated with the lut0910 extract. The histopathological changes of the tumor tissues showed that there were massive necrotic areas in the tumor tissues after treatment with different doses of the lut0910 extract. Our result would provide a new way and potent source for development of new anticancer agent from the polluted environment.